Clusia nubium (Clusiaceae): a new species from cloud-forests of southwestern Ecuador - Gustafsson, Mats H.g.; Borchsenius, Finn (Phytotaxa, 2016)
Clusia nubium from southwestern Ecuador is described as a species new to science. It grows as a hemiepiphyte in lower montane cloud forest. The species belongs to Clusia sect. Retinostemon, a largely Andean group characterized by male flowers with a resin-secreting synandrium of completely fused stamens and sometimes also anthers and staminodes. It differs from all other species in that section by the combination of creamy-white petals; male flowers with a dome-shaped synandrium with numerous fused stamens surrounding a group of resin secreting staminodia; and large fruits with 9–15 peltate stigmata forming a ring.